Kasih Kristus Sebagai Landasan Pengajaran Guru Kristen dalam Pendisiplinan Siswa [The Love of Christ as the Teaching Foundation for Christian Teachers in Disciplining Students] - Trinanda Adelvia Samben; Grace Purnamasari Christian (Universitas Pelita Harapan, 2021)
Love is essential in the life of a Christian. Love is not only expressed in words, but also through concrete actions. God Himself commands us believers to love God with all our heart and all mind and to love humans as ourselves. This love is what a Christian teacher needs in educating and disciplining students. A Christian teacher who loves God should also make love the foundation of his teaching. The love shown by a Christian teacher is not only about praising students, appreciating students, but also reprimanding students who make mistakes. The problem that often occurs is that teachers do not make love as the basis of their teaching, for example in teaching teachers still do physical and psychological violence to their students, give uneducative punishment, ignore students when they make mistakes. When the teacher does not make love the basis of his teaching, students will take part in learning because they are afraid of the teacher, students also do not respect the teacher and the teacher cannot touch the lives of their students. If a Christian teacher does not apply love as the basis of his teaching, Christian teachers will have difficulty introducing God to their students in their teaching. Seeing this problem, this paper aims to explain to Christian teachers the importance of making the love of Christ the foundation of teaching in student discipline. The research method used in writing papers is literature review.